Bantuan QuillBot dalam mendukung penulisan akademik bagi mahasiswa tingkat lanjut: Tinjauan sistematis literatur - Luh Rista Hardiantini; Ni Made Ratminingsih; I Gusti Ayu Lokita Purnamika Utami; Made Hery Santosa (Universitas Muhammadiyah Ponorogo, 2025)
QuillBot is a tool that influences the writing quality among higher students. This tool offers beneficial features that assist the development of academic writing ability among students. Therefore, this study aims to explore the assistance of QuillBot in academic writing among higher students. The researcher adopted the SLR (Systematic Literature Review) methodology proposed by Lame and Guillaume (2019). This method employs eight steps, from developing research questions to resulting interpretations. Those steps are conducted to determine whether the previous articles are appropriate and eligible. Ten articles were found that required the inclusion of the criteria. The articles were found in reputable resources such as Google Scholar, ResearchGate, ScienceDirect, and Taylor & Francis. The findings revealed that QuillBot assists the students in creating minimum errors in writing by discovering grammatical errors, paraphrasing sentences for writing evaluation, avoiding plagiarism, and encouraging students’ motivation. Overall, the tool facilitates the students’ development of their academic writing ability. Additionally, the students’ positive perceptions of writing development support it. They showed language improvement, such as vocabulary development and grammatical ability. Therefore, QuillBot assists the students in powering their writing ability and minimizing their anxiety toward academic writing.